Preliminary Study on Moisture, Fat, and Protein Contents of Bee Bread From Apis cerana from Different Regions in North Lombok Regency, Indonesia - Erwan Erwan; Lara Dwi Franti; Dwi Kusuma Purnamasari; Muhammad Muhsinin; Agussalim Agussalim (TERNAK TROPIKA Journal of Tropical Animal Production, 2021)
Apis cerana is one of the honeybee species from the Apis genus that produce honey, bee bread, royal jelly, and propolis. The objective of this study was to determine the honeybee forages as the pollen source and to evaluate the moisture, fat, and protein contents of bee bread from the bee of Apis cerana from different regions (Sigar Penjalin, Teniga, and Medana villages) in North Lombok, Indonesia. The methods used to determine the pollen source were taken flowers sample and then checking pollen at anther of flowers. The moisture, fat, and protein contents were determined using proximate analysis. The results showed that the honeybee forages as the pollen source from Sigar Penjalin village were maize, cashew, damar, kapok, calabash, breadfruit, passion fruit, and acacia. The plant flowers as the pollen source from Teniga village were coconut, coffee, cacao, citrus, guava, leucaena, papaya, and sugar palm, while those from Medana village were jackfruit, mangosteen, Java apple, maize, rice, candlenut, soybean, and banana. The moisture and fat contents of bee bread from Sigar Penjalin and Teniga villages were similar, and both were lower than the moisture and fat contents of bee bread from Medana village. The protein content of bee bread from Sigar Penjalin and Medana villages were similar, and both were lower than the protein content of bee bread from Teniga village. Thus, the bee bread from Teniga village was higher in protein content for all beekeeping regions, however Teniga village and Sigar Penjalin were similar in moisture and fat contents.